Accounting for substitution and spatial heterogeneity in a labelled choice experiment. (1st October 2016) - Lizin, S.; Brouwer, R.; Liekens, I.; Broeckx, S.
Abstract: Many environmental valuation studies using stated preferences techniques are single-site studies that ignore essential spatial aspects, including possible substitution effects. In this paper substitution effects are captured explicitly in the design of a labelled choice experiment and the inclusion of different distance variables in the choice model specification. We test the effect of spatial heterogeneity on welfare estimates and transfer errors for minor and major river restoration works, and the transferability of river specific utility functions, accounting for key variables such as site visitation, spatial clustering and income. River specific utility functions appear to be transferable, resulting in low transfer errors. However, ignoring spatial heterogeneity increases transfer errors. Highlights: Public preferences for river restoration are evaluated. Substitution effects and spatial heterogeneity are accounted for in a labelled choice experiment. Alternative specific utility functions are estimated and tested for their transferability. Parameter estimates are found to be transferable. Transfer errors are low, but increase when ignoring spatial heterogeneity.